1996
DOI: 10.1038/hdy.1996.157
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of powdery mildew resistance gene Pm8 in Triticum aestivum L. (common wheat) cultivars carrying wheat-rye tranlocation T1BL·1RS

Abstract: Disease response pattern of 127 T1B1RS translocation and substitution wheat cultivars, possessing powdery mildew resistance gene Pm8 and leaf rust resistance gene Lr26 located on rye chromosome arm iRS, revealed that sixteen of these cultivars express Lr26, but not concomitant Pm8 resistance. The mode of inheritance studied in the F1, F2 and F3 generations, and involving hybrids of cultivars Agra, Florida, Olymp, Sabina and Tjelvar not expressing Pm8 resistance indicated inhibition of resistance gene Pm8 by a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 17 publications
2
24
0
2
Order By: Relevance
“…Pm8 was suppressed at the seedling stage in certain 1B/ 1R translocation lines (Ren et al 1997;Hanusova et al 1996). The suppressor of Pm8 has been mapped to the short arm of chromosome 1A, and McIntosh et al (2011) recently demonstrated that Pm3 could act as a suppressor of the Pm8 resistance.…”
Section: Effect Of Race-specific Genesmentioning
confidence: 99%
“…Pm8 was suppressed at the seedling stage in certain 1B/ 1R translocation lines (Ren et al 1997;Hanusova et al 1996). The suppressor of Pm8 has been mapped to the short arm of chromosome 1A, and McIntosh et al (2011) recently demonstrated that Pm3 could act as a suppressor of the Pm8 resistance.…”
Section: Effect Of Race-specific Genesmentioning
confidence: 99%
“…Cluster 2: 22,7,30,21,23,19,27 Cluster 3: 17,12,8,5,4,24,11,28,16,14,15,6,1,9 Abb Auf Grund umfangreicher botanischer Untersuchungen gliederte Rechinger (Rechinger und Rechinger-Moser 1951;Rechinger 1943Rechinger , 1950 (Christodoulakis 1996a(Christodoulakis ,1996b (Bai und Knott 1992), Gelbrost (Kema et al 1995;Ma et al 1995) und Mehltau (Hanušova et al 1996) nachgewiesen werden.…”
Section: Bedeutung Und Nutzung Pflanzengenetischer Ressourcen In Der unclassified
“…Therefore, we suggest that the resistance gene(s) of 13-2-2 was inherited from rye and expressed in the common wheat (W770B) background. The resistance gene might be a novel resistance gene and different from Pm8 (Hanusova et al, 1996) and Pm17 (Heun and Fribe, 1990) located on 1RS. In the future, we intend to locate and map the powdery mildew resistance gene(s) by developing interbred populations.…”
Section: Discussionmentioning
confidence: 99%